The Mediterranean in check: Biological invasions in a changing sea - Giangrande, Adriana; Pierri, Cataldo; Del Pasqua, Michela; Gravili, Cinzia; Gambi, Maria Cristina; Gravina, Maria Flavia (Marine ecology (Berlin, West), 2020)
In recent decades, the high introduction rate of alien species (AS) has been mainly due to the increasingly widespread human movements, which often compromise natural barriers, facilitating the invasion of new geographic areas and environments. Being completely new in the recipient habitat, alien invasive species can often have strongly negative impacts on native communities, sometimes causing substantial and irreversible ecological and economic damage. Thus, AS have been branded as “negative” and are often targeted for eradication. However, an accurate assessment of ecological and economic impacts of alien taxa is still lacking in many species, and this is particularly true in marine environments. We focused on the Mediterranean Sea, a very important marine biodiversity “hot spot,” which is among the areas that have been most influenced by the arrival of non‐native species, a process also linked to global warming, leading to a deep transformation of this basin. We describe both negative and positive aspects of some well‐known introductions, assuming a different view of conservation. Biological invasions are, in fact, a fundamental and integral aspect of nature that has always been present in the history of life on Earth. Imagining that nature is static and needs to be restored to a particular state is not a reasonable way of looking at the processes of life. With this in mind, we argue that defining priorities in management and conservation is a prerogative that should not be based on the containment/eradication of one or another species, but on the conservation of those environmental conditions that are essential for the proper functioning of ecosystems. In other words, native versus non‐native species distinction cannot be the main guiding principle in conservation and restoration. For this reason, great attention must be paid to the containment of those human activities that cause greater pollution and rapid changes, and therefore threaten the habitats and biodiversity that we care about most.